Pengaruh Inflasi, Suku Bunga Dan Nilai Tukar Terhadap Harga Saham PT. Telekomunikasi Indonesia Tbk - Sulastri; Dedi Suselo (CV ODIS, 2022)
The number of people who are interested in investing in the Indonesian capital market, the number of investors is increasing every year. But many investors new or old are not careful when selling, buying, or holding stocks. To avoid risk, investors should analyze the company's macroeconomics. This study identifies several indicators, including inflation, exchange rates, and interest rates. The purpose of this study is to examine the effect of inflation, interest rates, and exchange rates on stock prices at PT. Indonesian Telecommunications. The sample in this study includes 1 company listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021 and was selected using the Target Sampling method (purposive sampling). This study uses analytical techniques using multiple linear regression analysis using the SPSS 16 program. The results of this study partially and simultaneously show that inflation, interest rates, and exchange rates have a significant influence on the company's stock price. Thus, some of these indicators can be taken into account by investors when making decisions about investing, selling, buying, and maintaining ownership of Shares.